Investigation on dielectric properties of sludge waste from water treatment using microwave non-destructive testing (MNDT) / Muhammad Al-Hadi Zable - Zable, Muhammad Al-Hadi (2024)
The discharge of wastewater into waterways, accounting for approximately 80% of the total volume, highlights the significance of exploring opportunities for recovering valuable resources from the wastewater. The management of sludge waste, a by-product of the water treatment process, presents a critical challenge that necessitates the development of sustainable and efficient solutions. The increase of sludge waste that remains after the water treatment process will require additional cost of handling and eventually will limit the landfilling area to dispose the sludge. Thus, this research study focuses to investigate the potential reuse of sludge waste from water treatment plants as a potential carbonised materials or to be used as fertilizers for land treatment. The main objective is to investigate the correlation between sludge and frequencies used to ensure the capability of the measurement method in measuring the sludge waste. The measurement setup utilized Microwave Non-Destructive Testing (MNDT), employing a free-space system at X-band frequencies comprising a vector network analyser and a pair of horn antennas. The extracted S-parameters from the measurement were subjected to rigorous analysis using statistical tools of the Statistical Package for the Social Sciences (SPSS). Next, is to study the characteristic of raw and dry sludge Sparameters in response of the X-band frequencies used. Samples of sludge were collected from two distinct water treatment plants, and drying process was employed over a period of four weeks, where the samples were dried and monitored on a weekly basis to replicate the sludge waste management procedure typically implemented in these plants. This is to capture the variations in the composition of the samples, measurements were taken at three different states: raw, granules, and dust. Lastly, an evaluation of dielectric properties of the sludge using Nicholson-Ross-Weir (NRW) conversion method was conducted. The subsequent step involved studying the dielectric properties of the sludge waste, aiming to comprehensively characterize the material.